2006
DOI: 10.1021/ie060580u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Alternative Flocculation System for Manufacture of Fiber−Cement Composites

Abstract: Flocculation has been a key issue for fiber cement manufacturing since cellulose or poly(vinyl alcohol) (PVA) fibers are used to replace asbestos. Due to the complexity of flocculation, many fiber cement companies face difficulties in optimizing it, which leads to unpredicted production problems and lower process efficiency. This paper studies the behavior of a dual system (PFR/PEO) and compares it with two anionic polyacrylamides commonly used in this industry. The work was carried out using a focused beam re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Negro et al [119] have shown that this effect is lower when the charge density of APAM increases and the molecular weight decreases. They have also proposed the use of alternative flocculants as dual systems formed by polyethylene oxide and phenolic resins [120,121].…”
Section: Further Applications To the C-fcc Production Processmentioning
confidence: 99%
“…Negro et al [119] have shown that this effect is lower when the charge density of APAM increases and the molecular weight decreases. They have also proposed the use of alternative flocculants as dual systems formed by polyethylene oxide and phenolic resins [120,121].…”
Section: Further Applications To the C-fcc Production Processmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] They are also deployed in the construction materials industry in order to tailor the rheology of these materials at the fresh state during the casting process. [16][17][18][19][20] As already stated, another important example can be found in EOR, where PAM/HPAM are used as mobility control agents. In this case, the adsorption of polymer onto mineral surfaces leads to an erosion of the viscous front and affect the injectivity process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, fiber cement composite production involves addition of PAM in order to tailor the flocculation properties to the casting process [1][2][3][4]. According to [5][6][7], PAM allows for an increase in the density of the resulting industrial product, which, in turn, is at the origin of an increase in mechanical strength.…”
Section: Introductionmentioning
confidence: 99%